2009
DOI: 10.1007/978-3-642-01793-3_31
|View full text |Cite
|
Sign up to set email alerts
|

Why Is Facial Occlusion a Challenging Problem?

Abstract: Abstract. This paper investigates the main reason for the obtained low performance when the face recognition algorithms are tested on partially occluded face images. It has been observed that in the case of upper face occlusion, missing discriminative information due to occlusion only accounts for a very small part of the performance drop. The main factor is found to be the registration errors due to erroneous facial feature localization. It has been shown that by solving the misalignment problem, very high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 21 publications
2
39
0
1
Order By: Relevance
“…During each session 13 pictures per person were taken under the same conditions. Similar to the work of [10], only a subset of 110 individuals for which all variability is available is used in our experiments. CMU-PIE.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During each session 13 pictures per person were taken under the same conditions. Similar to the work of [10], only a subset of 110 individuals for which all variability is available is used in our experiments. CMU-PIE.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for face detection and cropping [33], eye detection and subsequent rectification have been proposed. Using these methods, basic global transformations can be coped with, but it was shown that in addition strong features must be used in matching algorithms [10]. Matching algorithms try to find a matching local descriptor in the reference image for each item in a sparse or dense set of local descriptors representing the test image.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations